2015
DOI: 10.1080/09613218.2015.1052315
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem biomimetics for resource use optimization in buildings

Abstract: An ecomimetic method is developed as an innovative and transdisciplinary design approach rooted in the field of biomimetics. This new method emulates the interrelated complexity of the parts of an ecosystem with the intent to design buildings that are more efficient, effective and holistic. Ecomimetics refers to the design of buildings that mimic ecosystem processes and functions. This approach provides potential opportunities for climate change adaptation and mitigation by optimizing the use of resources in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…In this regard, nature-based solutions (NBS) have been rising as a sustainable way to both remove and recovery P from wastewaters. NBS promote an efficient use of natural resources, human well-being and a socially inclusive green growth by replicating natural process and integrating ecosystem services into the human environment [7][8][9]. Several authors have demonstrated that NBS, such as constructed wetlands (CWs) and biological filter beds are environmentally friendly and efficient at removing P from water [5,6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, nature-based solutions (NBS) have been rising as a sustainable way to both remove and recovery P from wastewaters. NBS promote an efficient use of natural resources, human well-being and a socially inclusive green growth by replicating natural process and integrating ecosystem services into the human environment [7][8][9]. Several authors have demonstrated that NBS, such as constructed wetlands (CWs) and biological filter beds are environmentally friendly and efficient at removing P from water [5,6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Not just for the buildings, but also for all urban areas. Several authors have been showing the positive impact of promoting the reconciliation of the urban environment and natural habitats, with regards to promoting biodiversity, increasing the resilience ability of the cities and climate change mitigation [24,33,34]. The potential interactions between green technologies and the environment may represent an important role, regarding closing the "cycle" and promoting a sustainable technological development.…”
Section: Wetwall and Circular Economymentioning
confidence: 99%
“…In this scope, ecomimetic designs (ED) and nature-based solution (NBS) have been considered as a promising strategies for climate change mitigation. ED and NBS, replicates features of natural systems to integrate ecosystem services into the human environment, and thus promote an efficient use of natural resources, a human well-being and a socially inclusive green growth [23,24]. According to Blok and Gremmen [25], "By using the same design principles as natural entities and systems, and by modelling our technological design on natural principles, biomimicry adheres to a bio-inclusive ethics that enables us to resituate our technological design within the ecological limits of the biosphere.…”
Section: Introductionmentioning
confidence: 99%
“…For example, investigations of terminologies from life sciences that could have similar use in buildings [55]; analyzing ecosystem interactions for higher sustainability and optimized resource use in the built environment [43,46,56]; exploring ideas from nature for inspiration [48]; and identifying strategies of animal skins for per-formative constructions [47]. Although these explorations reveal some unique aspects from nature to inform architecture, biomimetics as an effective design tool is still a challenge.…”
Section: Biomimeticsmentioning
confidence: 99%
“…Nature provides a large database of adaptation strategies that can be implemented in design in general, and in the design of building envelopes in particular. Several benefits are identified for applying biomimetics to solving building problems, such as enhancing creativity and innovation [40][41][42]; optimizing resource (i.e., materials and energy) use in buildings [43]; lowering pollution, benefiting health, and mitigating urban heat island effects [44]; and providing a foundation for environmentally responsive developments [45][46][47][48][49]. Two main approaches with various terminologies exist in biomimetics: (1) solution-based, where an observation of nature inspires a technological application; and (2) problem-based, where a solution from nature is sought for a particular engineering problem.…”
Section: Biomimeticsmentioning
confidence: 99%